Addiction and Virtue Beyond the Models of Disease and Choice (Strategic Initiatives in Evangelical Theology) - Dunnington, Kent (Downers Grove, Ill. IVP Academic, 2011)
What is the nature of addiction? Neither of the two dominant models (disease or choice) adequately accounts for the experience of those who are addicted or of those who are seeking to help them. In this interdisciplinary work, Kent Dunnington brings the n
Keywords: Habit breaking -- Religious aspects -- Christianity. Compulsive behavior -- Religious aspects -- Christianity. Church work with recovering addicts